(untitled) (Semiárida, 2020)
It has been evaluating range condition in twenty areas of shortgrasslands in Loventué - La Pampa. The state Condition’s identification was realized with the standing - crop’s dates. Frequency, density, cover and height of principal’s species were taken. The following indices were used to classified the grassland’s Condition: Very Good; Good, Fair, Poor and Very Poor.